Light Transduction in Invertebrate Hyperpolarizing Photoreceptors: Possible Involvement of a G(o)-Regulated Guanylate Cyclase - Gomez, Maria del Pilar (J Neurosci, 2000)
The hyperpolarizing receptor potential of scallop ciliary photoreceptors is attributable to light-induced opening of K(+)-selective channels. Having previously demonstrated the activation of this K(+) current by cGMP, we examined upstream events in the transduction cascade. GTP-γ-S produced persistent excitation after a flash, accompanied by decreased sensitivity and acceleration of the photocurrent, whereas GDP-β-S only inhibited responsiveness, consistent with the involvement of a G-protein. Because G(o) (but not G(t) nor G(q)) recently has been detected in the ciliary retinal layer of a related species, we tested the effects of activators of G(o); mastoparan peptides induced an outward current suppressible by blockers of the light-sensitive conductance such asl-cis-diltiazem. In addition, intracellular dialysis with the A-protomer of pertussis toxin (PTX) depressed the photocurrent. The mechanisms that couple G-protein stimulation to changes in cGMP were investigated. Intracellular IBMX enhanced the photoresponse with little effect on the baseline current, a result that argues against regulation by light of phosphodiesterase activity. LY83583, an inhibitor of guanylate cyclase (GC), exerted a reversible, dose-dependent suppression of the photocurrent. By contrast, ODQ, an antagonist of NO-sensitive GC, and YC-1, an activator of NO-sensitive GC, failed to alter the light response or the holding current; furthermore, the NO synthase inhibitor N-methyl-l-arginine was inert, indicating that the NO signaling pathway is not implicated. Taken together, these results suggest a novel type of phototransduction cascade in which stimulation of a PTX-sensitive G(o) may activate a membrane GC to induce an increase in cGMP and the consequent opening of light-dependent channels.